Abnormal Congenital Location of Stapes' Superstructure: Clinical and Embryological Implications. (28th August 2016) - Henriques, Vânia; Teles, Rafaela; Sousa, Ana; Estevão, Roberto; Rodrigues, Jorge; Gomes, Alexandra; Silva, Francisco; Fernandes, Ângelo; Fernandes, Fausto
Abstract : Congenital middle ear malformations are rare. Most part of them are usually associated with other malformations, such as aural atresia, microtia, and dysmorphic craniofacial features. A clinical case of a 24-year-old male with a right-sided conductive hearing loss since his childhood, without craniofacial malformation, is presented. He was proposed for exploratory tympanotomy under the suspicious diagnosis of otosclerosis. The surgery revealed an abnormal location of stapes' superstructure, which was attached to the promontory and had an isolated and mobile osseous footplate in the oval window. A stapes prosthesis was inserted and resulted in closure of the air-bone gap by 25 dB. A review of the literature was also performed using MEDLINE. Two theories diverge on the embryologic origin of the stapes. Our findings seem to be in favour of the theory that defines two different embryologic origins to the stapes.